2016
DOI: 10.9740/mhc.2016.09.248
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adherence in patients prescribed long-acting injectable antipsychotics: A comparison of biweekly versus monthly administered neuroleptics

Abstract: Background:Long-acting injectable antipsychotics (LAIAs) have been developed to decrease medication nonadherence. LAIAs are usually given biweekly or monthly, with the exception of new 3-month and 6-week formulations. There has been no known evaluation regarding whether the frequency of LAIA formulation affects adherence. The purpose of this study is to evaluate whether there is a difference in adherence between LAIAs administered biweekly or monthly.Methods:Eligible participants were identified from the Louis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…In addition, at least three considerations can be expressed. First, in line with our findings, haloperidol represents the most frequently administered compound in some community based-studies (Carr et al ., 2016; Grover et al ., 2019; Auxilia et al ., 2023). Nevertheless, it should be noted that available literature shows contrasting data about the preferential prescribed compound among LAI antipsychotic medications (Reymann et al ., 2022), in the light of different study methods and local factors (Barbui et al ., 2020).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, at least three considerations can be expressed. First, in line with our findings, haloperidol represents the most frequently administered compound in some community based-studies (Carr et al ., 2016; Grover et al ., 2019; Auxilia et al ., 2023). Nevertheless, it should be noted that available literature shows contrasting data about the preferential prescribed compound among LAI antipsychotic medications (Reymann et al ., 2022), in the light of different study methods and local factors (Barbui et al ., 2020).…”
Section: Discussionsupporting
confidence: 91%
“…Even though the available literature shows contrasting data about the preferential prescribed compound among LAI antipsychotics [15,31], guidelines do not provide recommendations on which LAI should be selected, suggesting that the same criteria recommended for the choice of an oral antipsychotic be taken into account. Notably, haloperidol was found to represent the most frequently administered compound, in line with previous reports [34,35]. Taking into account real-world data from recent studies, to the best of our knowledge, this is the first study showing higher prescription of haloperidol decanoate as compared to other LAI antipsychotics.…”
Section: Discussionsupporting
confidence: 88%
“…From a patient’s perspective, a formulation like PP3M is advantageous, as they need to visit clinics less frequently for injections, especially benefiting patients who are away from home or traveling, etc. As studies have shown a lack of any significant adherence advantage with monthly injected LAIs, it is important to investigate correlations between observed patient preference and positive attitudes on measurement of actual medication adherence in patients using PP3M 113…”
Section: Review Of Evidencementioning
confidence: 99%